Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Can unmanned aerial vehicle laser scanning serve as an effective alternative to traditional field methods for predicting tree growth in even-aged Chinese fir (Cunninghamia lanceolata) plantations? - Rui Li; Baoying Wang; Ruiting Liang; Zhidan Ding; Zhaoting Zhu; Yujun Sun (European Journal of Forest Research, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Identification of potential mechanisms of quercetin in diabetic peripheral neuropathy through integrated network pharmacology and experimental validation - Zanpeng Chen; Ziyu Li; Xiaowei Xue; Wei Song; Rui Zhang; Chao Wang; Bin Yan; Qing Sun; Qunli Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Non-nitrogen-fixing halophytes alleviate nitrogen limitation and decrease soil salinity through nitrogen transfer from nitrogen-fixing plants - Zehao Zhang; Tian Li; Yao Zhang; Rui Hu; Jiabao Li; Hongxiang Jin; Ying Fang; Zhaohua Lu; Jingkuan Sun (Plant and Soil, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

GPx6 downregulation drives ferroptosis in Kashin-Beck disease chondrocytes via the SLC7A11/GPx4 axis - Yinan Liu; Jie Li; Meng Zhang; Ying Zhang; Mengying Wang; Rui Wang; Xiaoming Zhao; Pinglin Yang; Jinghong Chen; Jian Sun (Apoptosis, 2026)

Enhanced deep nitrogen removal from low C/N wastewater via manganese-catalyzed iron-carbon micro-electrolysis coupled biological system: performance, mechanism, and microbial adaptability - Hengyuan Liu; Kai Wang; Feng Sha; Haibing Che; Rui Sun; Xiuhua Li (World Journal of Microbiology and Biotechnology, 2026)

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

Research on Dynamic Control of Flood Control Level for Jinxia Reservoir Group Considering Risks - Min Li; Yue Sun; Rui Feng; Wei Ding; Qianning Wang; Jinnan Zhang; Yong Peng; Feilin Zhu (Water Resources Management, 2026)

Green conversion of coal gangue acid leaching residue into a K2Si4O9 fertilizer material: a sustainable strategy for solid waste upcycling - Junli Zhang; Zhumei Sun; Yucen Gao; Ying Li; Rui Ma; Yanfang Chai; Haifang Wang (Waste Disposal & Sustainable Energy, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Responses of soil nitrogen mineralization to ecological restoration-oriented constructed grasslands with different recovery ages in the Three-River Headwaters Region - Jie Zhu; Baolin Li; Guoyi Zhou; Yecheng Yuan; Wei Liu; Rui Li; Qiuyuan Tan; Qingling Sun (Plant and Soil, 2026)

Analysis of the species distribution and drug resistance of pathogenic microorganisms causing diabetic foot infections in Southwest China from 2020 to 2024: a retrospective cross-sectional analysis - Shangyu Zhang; Junchi Chen; Rui Sun; Yu Pan; Yusen Zhuo; Li Tang; Jianhua Zhu; Shuyang Li; Lin Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Molecular Basis of Biostimulant-enhanced Recovery from Late-spring Frost in Vitis Vinifera: A Transcriptomic Dissection - Chaoyue Feng; Xi Chen; Xinyi Luo; Huiyu Zhu; Huiling Ma; Xiaojun Liu; Yulong Li; Quan Sun; Rui Wang; Yaqi Wang (Journal of Plant Growth Regulation, 2026)

What are the driving factors and spatial-temporal characteristics of the landscape ecological risk of the Yellow River Delta? - Yao Zhang; Rui Hu; Tian Li; Zehao Zhang; Zhanyong Fu; Kaikai Dong; Jinzhao Ma; Zhaohua Lu; Jingkuan Sun (Environment, Development and Sustainability, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Exploring factors influencing the height growth of Cunninghamia lanceolata based on bootstrap bayesian network and random forest - Baoying Wang; Rui Li; Yujun Sun; Ruiting Liang; Zhaoting Zhu (Trees, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Selenium-Enriched Akkermansia muciniphila: A Novel Probiotic Bacterium for Se Supplementation - Wen Rui; Yuhang Sun; Xiaoqian Li; Jingpeng Yang; Xuna Tang (Probiotics and Antimicrobial Proteins, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

ADAM17 Supports Disinhibition of Pre-sympathetic Glutamatergic Neurons Through Microglial Chemotaxis - Jiawei Wang; Zihan Qiu; Yue Han; Hanxue Wu; Miao Yuan; Yan Liu; Huichao Wang; Shenglan Yuan; Dengfeng Gao; Lina Sun; Xingjuan Chen; Eric Lazartigues; et al. (Neuroscience Bulletin, 2026)

Potential Therapeutic Effects of Astragaloside IV in Parkinson’s Disease Models via Modulation of α-syn-γH2AX-STING-IFN-I Axis - Rui Wang; Fengjiao Sun; Nan Wang; Fang Chen; Xianzhi Wang; Chen Li; Hongcai Wang (Molecular Neurobiology, 2026)

Associations of Paternal Seminal Plasma Metals with their Spouses’ Unexplained Recurrent Spontaneous Abortion (URSA) Risk and the Potential Mediating Role of Oxidative Stress - Hanyan Xi; Rui Yang; Huaqiong Bao; Huiru Li; Youzhu Li; Francis L. Martin; Wei Chen; Liang Chen; Yan Sun; Yan-Yang Lu; Qingyu Huang; Meiping Tian (Biological Trace Element Research, 2025)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Detection of Caco-2 cell absorption rate of Bombyx mori peptide chelated zinc and validation of anti-inflammatory activity based on network pharmacology - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun; Fengqing Zhang (BioMetals, 2025)

A block theory-based method for identifying the boundaries and movement modes of potential unstable bodies in rock slopes - Qinkuan Hou; Shuhong Wang; Rui Yong; Zong Li; Wenshuai Han; Wenpan Sun (Rock Mechanics and Rock Engineering, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Efficacy Evaluation of Selenium-enriched Akkermansia muciniphila in the Treatment of Colon Tumor Mice - Xiaoqian Li; Wen Rui; Pingting Shu; Yuhang Sun; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2025)

Sinomenine enhances recovery from corneal alkali burns by attenuating macrophage M1 polarization through modulating the METTL3/IRAKM axis - Jun-qi Li; Rui-ze Sun (Journal of Molecular Histology, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Associations Between Metal–Metal Interaction and the Risk of Hypertension: A Case–Control Study in Chinese Community-Dwelling Elderly - Meiyan Li; Yihong Di; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Yuqing Dai; Zhuoheng Shen; Yue Chen; Huifang Yang; Xiaoyu Li; Jian Sun; et al. (Cardiovascular Toxicology, 2025)

Antimicrobial Peptides: Classification, Mechanism, and Application in Plant Disease Resistance - Yuan-Zhen Wu; Jin Wang; Ying-Hui Hu; Qi-Shuo Sun; Rui Geng; Li-Na Ding (Probiotics and Antimicrobial Proteins, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Digitalization and sustainable development: How could digital economy drive circular economy development in China? - Yingshan Sun; Rui Zhang; Xiaotong Qie; Dongxue Li; Xiaoyi Zhang; Xiaolu Du; Yue Wang (Environment, Development and Sustainability, 2025)

Gut microbiota’s role in high-altitude cognitive impairment: the therapeutic potential of Clostridium sp. supplementation - Wei Zhou; Yongqiang Zhou; Shikun Zhang; Bin Li; Zhong Li; Zhijie Bai; Dezhi Sun; Chaoji Huangfu; Ningning Wang; Tiantian Xia; Congshu Huang; Lina Guan; et al. (Science China Life Sciences, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Paeoniflorin-mediated downregulation of VEGFA: unveiling the therapeutic mechanism of buyang huanwu decoction in diabetic retinopathy - Wentao Sun; Rui Wang; Ke Gong; Liping Wang; Fengzhi Li; Jin Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

Distribution and ecological risks of microplastics in a tropical tourism island area in Hainan, China - Weijie Bian; Rui Sun; Yurui Li; Shuguo Lü; Dongwei Yang; Hongbo Li; Yingxu Zeng; Min Liu (Journal of Oceanology and Limnology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Transcriptome Analysis Reveals the lncRNA-mRNA Co-expression Network Regulating the Aestivation of Sea Cucumber - Xiaomei Chen; Wentao Han; Rui Yang; Xuan Zhu; Shengwen Li; Yangfan Wang; Xue Sun; Yuli Li; Lisui Bao; Lingling Zhang; Shi Wang; Jing Wang (Marine Biotechnology, 2025)

Associations of phthalate and phthalate alternative metabolites in urine with the risk of gallstones in adults: a cross-sectional analysis - Tianshan Shi; Di Li; Donghua Li; Peng Xie; Jin Sun; Tingrong Wang; Rui Li; Zixuan Zou; Zhenjuan Li; Xiaowei Ren (Environmental Geochemistry and Health, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Antibacterial Effect and Network Pharmacology Mechanism of Male Bombyx mori. on Escherichia Coli - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun (International Journal of Peptide Research and Therapeutics, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

The Influence of pH on Sulfamethoxazole in Soil Systems: Migration and Degradation - Haifang Wang; Xin Li; Zhumei Sun; Xia Cao; Junli Zhang; Qihua Chen; Rui Ma (Water, Air, & Soil Pollution, 2024)

Deep Learning Based Diagnosis of Mild Cognitive Impairment Using Resting-State Functional MRI - Guangyao Li; Yalin Song; Huimin Liang; Xiaoman Sun; Junyang Yu; Rui Zhai; Mingyang Liang (Journal of Medical and Biological Engineering, 2024)

Tree characteristics, drought and microtopography modulate the response of subtropical Cunninghamia lanceolata to drought - Ruiting Liang; Yujun Sun; Zhaoting zhu; Rui Li (European Journal of Forest Research, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Deep structure of the Kumkol basin in the northern Tibetan Plateau and its resource environmental implications - Wenhui Li; Zhanwu Lu; Rui Gao; Xiaofan Deng; Jingyuan Li; Guangwen Wang; Zhanxuan Sun (Science China Earth Sciences, 2024)

Association Between Zinc Ion Concentrations in Seminal Plasma and Sperm Quality: A Chinese Cross-Sectional Study - Gangxin Chen; YeBin Feng; Rui Yang; Haiyan Li; Zhiqin Huang; Zhihao Li; Beihong Zheng; Yan Sun (Biological Trace Element Research, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Green Approach for Simultaneous Quantitative Analysis of Fluoroquinolones in the Environment using Three-Dimensional Fluorescence Coupled with Second-Order Calibration Method - Yuping Yao; Liyan Song; Lingli Jiang; Mengfan Sun; Rui Li; Zhongze Zhou; Yuanna Li (Journal of Fluorescence, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Investigation of the effects and mechanisms of manganese-based NMs on rice growth - Yaqi Jiang; Yi Sun; Peng Zhang; Pingfan Zhou; Qibin Wang; Guikai Zhu; Weichen Zhao; Yuanbo Li; Quanlong Wang; Yukui Rui (Environmental Science and Pollution Research, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Correlation and interaction between urinary metals level and diabetes: A cross sectional study of community-dwelling elderly - Rui Wang; Pei He; Siyu Duan; Zhongyuan Zhang; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Yanan Song; Yiping Sun; Rui Zhang; Jian Sun; et al. (Exposure and Health, 2024)

Scientometric analysis of electrocatalysis in wastewater treatment: today and tomorrow - Qianqian Li; Xiaoya Fang; Lili Jin; Xiangzhou Sun; Hui Huang; Rui Ma; Han Zhao; Hongqiang Ren (Environmental Science and Pollution Research, 2024)

Corrosion of Q235 carbon steel induced by sulfate-reducing bacteria in groundwater: corrosion behavior, corrosion product, and microbial community structure - Wenxin Hua; Rui Sun; Xiaoyan Wang; Yunyun Zhang; Jiaxing Li; Ri Qiu; Yu Gao (Environmental Science and Pollution Research, 2023)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

Improvement of Soil Structure and Bacterial Composition by Long-Term Application of Seaweed Fertilizer - Liu Qiqin; Zhou Huaguang; Sun Minxiu; Li Qian; Fan Haijun; Chen Haimin; Yang Rui (Journal of Soil Science and Plant Nutrition, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Acylhydrazone Functionalized Triphenylamine-Based Fluorescent Probe for Cu2+: Tunable Structures of Conjugated Bridge and Its Practical Application - Xiaohong Cheng; Rui Zhang; Jinbo Sun; Ke Xu; Wangnan Li (Journal of Fluorescence, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Study on the correlation and interaction between metals and dyslipidemia: a case–control study in Chinese community-dwelling elderly - Zhongyuan Zhang; Rui Wang; Pei He; Yuqing Dai; Siyu Duan; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Jian Sun (Environmental Science and Pollution Research, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

Performance of Zeolite and Trace Elements on Biogas Production from Alkaline Hydrogen Peroxide–Pretreated Sweet Sorghum Bagasse Slurry - Xuemei Li; Ying Xiao; Rui Zhang; Chen Sun; Weixing Cao (BioEnergy Research, 2023)

Resistivity responses of sodium sulfate and sodium chloride-type loess under different water and salinity conditions - Xiaoran Li; Qiang Sun; Xusheng Yan; Pengfei Li; Rui Lv (Environmental Science and Pollution Research, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

3D gravity anomaly inversion based on LinkNet - Hou-Pu Li; Rui Qi; Jia-Xin Hu; Yu-Xin Sun (Applied Geophysics, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Electroacupuncture promotes remyelination and alleviates cognitive deficit via promoting OPC differentiation in a rat model of subarachnoid hemorrhage - Yingwen Wang; Xiaomin Yang; Yunchuan Cao; Xiaoguo Li; Rui Xu; Jin Yan; Zongduo Guo; Shanquan Sun; Xiaochuan Sun; Yue Wu (Metabolic Brain Disease, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Channeling analysis of wavelet threshold processing based on K-means clustering algorithm - Lixiong Gan; Ming Li; Wenyuan Cai; Jian Li; Zhanglong Chen; Jian Sun; Rui Deng (Acta Geophysica, 2023)

The effect of precipitation timing on phylogenetic and functional community structure in a semi-arid steppe - Zhongling Yang; Manman Wang; Jianwen Yang; Rui Xiao; Chen Miao; Yanfeng Sun; Tong Zhang; Guoyong Li (Oecologia, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Removal performance and mechanisms of Pb(II) and Sb(V) from water by iron-doped phosphogypsum: single and coexisting systems - Xinyue Ma; Qiao Li; Rui Li; Wei Zhang; Xiuyun Sun; Jiansheng Li; Jinyou Shen; Weiqing Han (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Human Urine-Derived Stem Cells Improve Partial Bladder Outlet Obstruction in Rats: Preliminary Data and microRNA-mRNA Expression Profile - Menjiang Tu; Rui Wang; Pei Zhu; Qingqing Wang; Bishao Sun; Keshi Lu; Jiawei Zhang; Weijie Xie; Huan Guo; Shulin Li; Yuqi Wu; Xiangwei Wang (Stem Cell Reviews and Reports, 2022)
Partial bladder outlet obstruction (pBOO) often results in bladder tissue inflammation and remodeling. As human urine-derived stem cells (USCs) have demonstrated therapeutic benefits, we used a rat model to investigate the effect of USCs on bladder function and explore the miRNA and gene expression profiles in bladder tissue using RNA sequencing. Eighteen rats were assigned to a sham surgery group, pBOO group, and pBOO+USC group (six biweekly treatments). Routine urodynamic monitoring, analysis of detrusor muscle strips, and pathophysiology assessments were conducted. Finally, altered miRNA and mRNA expression profiles of bladder tissue were examined using RNA sequencing and bioinformatics analysis. After USC treatment, elevated bladder compliance and maximal voiding pressure, declined end filling pressure and voided volume, and improved detrusor muscle contractility and carbachol sensitivity were found. Histology and TUNEL assay revealed reduced collagen deposition and muscle cell apoptosis in bladder tissue. The differential expression of eight miRNAs was reversed by USC treatment. Two large nodes (miR-142 and miR-9a) were identified in the miRNA-gene interaction network in the USC-treated group. The Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment of multiple significant pathways, including those involved in necroptosis and cytokine-cytokine receptor interactions. This is the first study to demonstrate the protective effect of USCs on bladder function and remodeling in pBOO rats. The miRNA and mRNA expression levels differed in the bladder of pBOO rats with and without USC treatment. Although the mechanism underlying these effects has not been fully elucidated, necroptosis and cytokine-cytokine receptor interaction-related pathways may be involved. Graphical abstract

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Outdoor air pollution exposure and the risk of asthma and wheezing in the offspring - Lei Hua; Liangliang Ju; Hanbing Xu; Changlian Li; Shu Sun; Qi Zhang; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

Molecular Characterization, Expression Pattern and Transcriptional Regulation of Figla During Gonad Development in Japanese Founder (Paralichthys olivaceus) - Jiangbo Qu; Rui Li; Yuxiang Liu; Minmin Sun; Weijie Yan; Jinxiang Liu; Xubo Wang; Quanqi Zhang (Journal of Ocean University of China, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

The functional evolution and system equilibrium of urban and rural territories - Jie Fan; Sisi Li; Zhongrui Sun; Rui Guo; Kan Zhou; Dong Chen; Jianxiong Wu (Journal of Geographical Sciences, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

China’s food security situation and key questions in the new era: A perspective of farmland protection - Xinyuan Liang; Xiaobin Jin; Bo Han; Rui Sun; Weiyi Xu; Hanbing Li; Jie He; Jin Li (Journal of Geographical Sciences, 2022)

AT1 Receptors: Their Actions from Hypertension to Cognitive Impairment - Hanxue Wu; Qi Sun; Shenglan Yuan; Jiawei Wang; Fanni Li; Hongli Gao; Xingjuan Chen; Rui Yang; Jiaxi Xu (Cardiovascular Toxicology, 2022)

Alleviative Effects of Exercise on Bone Remodeling in Fluorosis Mice - Rui Li; Zeen Gong; Yanghuan Yu; Ruiyan Niu; Shengtai Bian; Zilong Sun (Biological Trace Element Research, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Organic-rich formation and hydrocarbon enrichment of lacustrine shale strata: A case study of Chang 7 Member - Quanyou Liu; Peng Li; Zhijun Jin; Yuewu Sun; Guang Hu; Dongya Zhu; Zhenkai Huang; Xinping Liang; Rui Zhang; Jiayi Liu (Science China Earth Sciences, 2022)

Prenatal air pollution exposure increases the risk of macrosomia: evidence from a prospective cohort study in the coastal area of China - Changlian Li; Liangliang Ju; Mei Yang; Qi Zhang; Shu Sun; Jiyu Cao; Rui Ding (Environmental Science and Pollution Research, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

Structure and variation of root-associated bacterial communities of Cyperus rotundus L. in the contaminated soils around Pb/Zn mine sites - Pin Gao; Benru Song; Rui Xu; Xiaoxu Sun; Hanzhi Lin; Fuqing Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2021)

Multistage geomorphic evolution of the Central Canyon in the Qiongdongnan Basin, NW South China Sea - Chao Li; Guojun Chen; Qianshan Zhou; Chengze Li; Rui Sun; Chengfu Lyu; Shuai Guo (Marine Geophysical Research, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Synthesis of efficient Y-Bi2WO6/G visible light photocatalysts with high stability for pollutant degradation - Rui Sun; Risheng Li; Shuang Zhong; Ningning Song; Zhiqing Zhao; Shengyu Zhang (Environmental Science and Pollution Research, 2021)

Catalytic Hydroprocessing of White Pine Pyrolysis Bio-Oil over Cobalt-Molybdenum Carbide in a Continuous Packed-Bed Reactor - Rui Li; Zhixin Zhao; Bo Zhang; Xiaozheng Sun; Zhen Zhang; Ying Zhang; Haitao Chen; Qiangu Yan (BioEnergy Research, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

GmNAC06, a NAC domain transcription factor enhances salt stress tolerance in soybean - Ming Li; Rui Chen; Qiyan Jiang; Xianjun Sun; Hui Zhang; Zheng Hu (Plant Molecular Biology, 2021)
Key message We found GmNAC06 plays an important role in salt stress responses through the phenotypic, physiological and molecular analyses of OE, VC, and Mutant composite soybean. Abstract Salinization affects 20% of all cultivated land worldwide because of the high salinity of irrigation water and the excessive use of water, and this amount is increasing daily. NAC (NAM, ATAF, and CUC) have been found to be involved in salt stress. In this study, a soybean NAC gene, GmNAC06 (Glyma06g21020.1), was cloned and functionally characterized. The results of expression analysis suggested that salt stress could influence the expression level of GmNAC06 . The subcellular localization analysis results suggested that GmNAC06 may function as a transcription factor. Under salt stress, the overexpression technology combined with CRISPR-Cas9 system found that GmNAC06 could cause the accumulation of proline and glycine betaine to alleviate or avoid the negative effects of ROS; similarly, it could control the Na + /K + ratios in hairy roots to maintain ionic homeostasis. The fresh weight of the transgenic hairy roots and the histochemical ROS staining of wild leaves suggested that transgenic hairy roots influence the function of wild leaves under salt stress conditions. Moreover, the expression levels of GmUBC2 and GmHKT1 were higher in the GmNAC06 hairy roots than in the control. Thus, the overexpression of GmNAC06 in hairy roots notably causes an entire composite plant to exhibit salt tolerance. The phenotype of composite soybean plants and transgenic Arabidopsis plants suggest that GmNAC06 plays a role in response to salt stress and could be useful in generating salt tolerant transgenic crops.

Functional characterization of the MiR171a promoter and endogenous target mimics identification in Lilium pumilum DC. Fisch. during somatic embryogenesis - Hongyu Li; Jing Wang; Rui Yan; Chunxia Wang; Hongmei Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Control effects of the synsedimentary faults on the basin-marginal fans in the central part of the deep-water area of early Oligocene Qiongdongnan Basin, South China Sea - Guangzeng Song; Zengxue Li; Haizhang Yang; Dongdong Wang; Ying Chen; Rui Sun (Acta Oceanologica Sinica, 2021)

Isoorientin exerts a urate-lowering effect through inhibition of xanthine oxidase and regulation of the TLR4-NLRP3 inflammasome signaling pathway - Meng-Fei An; Ming-Yue Wang; Chang Shen; Ze-Rui Sun; Yun-Li Zhao; Xuan-Jun Wang; Jun Sheng (Journal of Natural Medicines, 2021)

The short-term effect of PM2.5/O3 on daily mortality from 2013 to 2018 in Hefei, China - Xinmiao Sui; Junqing Zhang; Qi Zhang; Shu Sun; Ruoqian Lei; Chao Zhang; Han Cheng; Liu Ding; Rui Ding; Changchun Xiao; Xiaoru Li; Jiyu Cao (Environmental Geochemistry and Health, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Cloning and expression of Allophycocyanin gene from Gracilariopsis lemaneiformis and studying the binding sites of phycocyanobilin on its α and β subunits - Yalin Guo; Xiaonan Zang; Xuexue Cao; Feng Zhang; Deguang Sun; Menghui Shang; Rui Li; Zhaxi Yangzong; Xuehong Wei; Xuecheng Zhang (Journal of Applied Phycology, 2020)

Efficient removal of tylosin by nitrogen-doped mesoporous carbon nanospheres with tunable pore sizes - Xingru Hu; Junwen Qi; Rui Lu; Xiuyun Sun; Jinyou Shen; Weiqing Han; Lianjun Wang; Jiansheng Li (Environmental Science and Pollution Research, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Visible and near-infrared spectroscopy with chemometrics are able to predict soil physical and chemical properties - Jinbao Liu; Jiancang Xie; Jichang Han; Huanyuan Wang; Jianhong Sun; Rui Li; Shaoxuan Li (Journal of Soils and Sediments, 2020)

MiR-430 Can Affect the Mesoderm Formation and Metamorphosis of Paralichthys olivaceus by Targeting lefty Gene - Rui Li; Zhenwei Wang; Minmin Sun; Meiting Peng; Jie Qi; Zhigang Wang (Journal of Ocean University of China, 2020)

Short-term effects of particulate matter exposure on emergency room visits for cardiovascular disease in Lanzhou, China: a time series analysis - Rui Chen; Qian Gao; Jianyun Sun; Haixia Yang; Yongjun Li; Fenyan Kang; Wei Wu (Environmental Science and Pollution Research, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Systematic analysis of lncRNA expression profiles and atherosclerosis-associated lncRNA-mRNA network revealing functional lncRNAs in carotid atherosclerotic rabbit models - Yingnan Wu; Feng Zhang; Xiaoying Li; Wenying Hou; Shuang Zhang; Yanan Feng; Rui Lu; Yu Ding; Litao Sun (Functional & Integrative Genomics, 2020)

Biochar-related studies from 1999 to 2018: a bibliometrics-based review - Dongyang Li; Rui Zhao; Xing Peng; Zhifei Ma; Ying Zhao; Tiancheng Gong; Mengyang Sun; Yuxin Jiao; Tianxue Yang; Beidou Xi (Environmental Science and Pollution Research, 2020)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Application of the SeDeM Expert System in Studies for Direct Compression Suitability on Mixture of Rhodiola Extract and an Excipient - Shulin Wan; Rui Yang; Han Zhang; Xuelian Li; Mingxian Gu; Tianbing Guan; Jianbing Ren; Huimin Sun; Chuanyun Dai (AAPS PharmSciTech, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Correction to: Genome-wide analysis of the MYB-CC gene family of maize - Jianrong Bai; Fengjie Sun; Minglei Wang; Liang Su; Rui Li; Gustavo Caetano-Anollés (Genetica, 2019)

Genome-wide analysis of the MYB-CC gene family of maize - Jianrong Bai; Fengjie Sun; Minglei Wang; Liang Su; Rui Li; Gustavo Caetano-Anollés (Genetica, 2019)

Iron plaque formation on wetland-plant roots accelerates removal of water-borne antibiotics - Yiping Tai; Nora Fung-Yee Tam; Rui Wang; Yang Yang; Jianhua Lin; Jiaxi Wang; Yufen Yang; Li Li; Yaoming Sun (Plant and Soil, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Effects of Fluoride on SOD and CAT in Testis and Epididymis of Mice - Zilong Sun; Sujuan Li; Zhenzhen Guo; Rui Li; Jixiang Wang; Ruiyan Niu; Jundong Wang (Biological Trace Element Research, 2018)

Low-level concentrations of aminoglycoside antibiotics induce the aggregation of cyanobacteria - Lin-Rui Tan; Peng-Fei Xia; Raymond J. Zeng; Qian Li; Xue-Fei Sun; Shu-Guang Wang (Environmental Science and Pollution Research, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Genetic diversity and phylogenetic analysis of Aleutian mink disease virus isolates in north-east China - Xue Leng; Dongxu Liu; Jianming Li; Kun Shi; Fanli Zeng; Ying Zong; Yi Liu; Zhibo Sun; Shanshan Zhang; Yadong Liu; Rui Du (Archives of Virology, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Crystal fractionation of granitic magma during its non-transport processes: A physics-based perspective - Chen Chen; Xing Ding; Rui Li; WeiQi Zhang; DongJian Ouyang; Lei Yang; WeiDong Sun (Science China Earth Sciences, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

Variable-grid reverse-time migration of different seismic survey data - Xiao-Dong Sun; Zhen-Chun Li; Yan-Rui Jia (Applied Geophysics, 2017)

Evaluation of bioaugmentation and biostimulation on arsenic remediation in soil through biovolatilization - Peng Chen; Jin Li; Hong-Yan Wang; Rui-Lun Zheng; Guo-Xin Sun (Environmental Science and Pollution Research, 2017)

Effects of Cd on reductive transformation of lepidocrocite by Shewanella oneidensis MR-1 - Chaolei Yuan; Fangbai Li; Rui Han; Tongxu Liu; Weimin Sun; Weilin Huang (Acta Geochimica, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

The effect of Mg2+ on digestion performance and microbial community structures in sludge digestion systems - CongCong Liu; Cheng Huang; XiuYun Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Lianjun Wang (Environmental Science and Pollution Research, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Effects of Cold Stress on Root Growth and Physiological Metabolisms in Seedlings of Different Sugarcane Varieties - Bo Sun; Guang-Ling Liu; Thi Thu Phan; Li-Tao Yang; Yang-Rui Li; Yong-Xiu Xing (Sugar Tech, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Genotoxicity and cytotoxicity reduction of the polluted urban river after ecological restoration: a field-scale study of Jialu River in northern China - Jie Sun; Rui Zhang; Long Qin; Haixiao Zhu; Yu Huang; Yingang Xue; Shuqing An; Xianchuan Xie; Aimin Li (Environmental Science and Pollution Research, 2017)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

Augmented expression of gamma-glutamyl transferase 5 (GGT5) impairs testicular steroidogenesis by deregulating local oxidative stress - Wei Li; Zhi-qun Wu; Shun Zhang; Rui Cao; Jie Zhao; Zhi-jian Sun; Wei Zou (Cell and Tissue Research, 2016)

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Exogenous Abscisic Acid Alleviates Cadmium Toxicity by Restricting Cd2+ Influx in Populus euphratica Cells - Yansha Han; Shaojie Wang; Nan Zhao; Shurong Deng; Chenjing Zhao; Nianfei Li; Jian Sun; Rui Zhao; Huilan Yi; Xin Shen; Shaoliang Chen (Journal of Plant Growth Regulation, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Extracellular ATP mediates cellular K+/Na+ homeostasis in two contrasting poplar species under NaCl stress - Nan Zhao; Shaojie Wang; Xujun Ma; Huipeng Zhu; Gang Sa; Jian Sun; Nianfei Li; Chenjing Zhao; Rui Zhao; Shaoliang Chen (Trees, 2016)

A new thalloid liverwort: Pallaviciniites sandaolingensis sp. nov. from the Middle Jurassic of Turpan–Hami Basin, NW China - Rui-Yun Li; Xue-lian Wang; Jing-Wei Chen; Sheng-Hui Deng; Zi-Xi Wang; Jun-Ling Dong; Bai-Nian Sun (PalZ, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Hydrolysis and volatile fatty acids accumulation of waste activated sludge enhanced by the combined use of nitrite and alkaline pH - Cheng Huang; Congcong Liu; Xiuyun Sun; Yinglu Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Xiaodong Liu; Lianjun Wang (Environmental Science and Pollution Research, 2015)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Vegetation physiological parameter setting in the Simple Biosphere model 2 (SiB2) for alpine meadows in the upper reaches of Heihe river - Yuan Li; Rui Sun; ShaoMin Liu (Science China Earth Sciences, 2015)

Cloning and expression analysis of phenylalanine ammonia-lyase (PAL) gene family and cinnamate 4-hydroxylase (C4H) from Dryopteris fragrans - Yan Li; Lili Sun; Hemeng Wang; Rui Gao; Junzheng Zhang; Baozhong Hu; Ying Chang (Biologia, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Simultaneous inversion of petrophysical parameters based on geostatistical a priori information - Xing-Yao Yin; Rui-Ying Sun; Bao-Li Wang; Guang-Zhi Zhang (Applied Geophysics, 2014)

Seohaeicola westpacificensis sp. nov., A Novel Member of Genera Seohaeicola Isolated from Deep West Pacific Sea Water - Shuhui Xian; Rui Zhang; Jia Sun; Yi Chen; Wenchao Deng; Shuhui Li; Nianzhi Jiao (Current Microbiology, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

Screening of Actinobacillus pleuropneumoniae LuxS Inhibitors - Lu Li; Lili Sun; Yunfeng Song; Xinjuan Wu; Xuan Zhou; Ziduo Liu; Rui Zhou (Current Microbiology, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Regulation of phenylalanine ammonia-lyase (PAL) gene family in wood forming tissue of Populus trichocarpa - Rui Shi; Christopher M. Shuford; Jack P. Wang; Ying-Hsuan Sun; Zhichang Yang; Hsi-Chuan Chen; Sermsawat Tunlaya-Anukit; Quanzi Li; Jie Liu; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2013)

Arm–eye coordination test to objectively quantify motor performance and muscles activation in persons after stroke undergoing robot-aided rehabilitation training: a pilot study - Rong Song; Kai-Yu Tong; Xiaoling Hu; Le Li; Rui Sun (Experimental Brain Research, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

A miR-570 binding site polymorphism in the B7-H1 gene is associated with the risk of gastric adenocarcinoma - Weipeng Wang; Fang Li; Yong Mao; Huan Zhou; Jing Sun; Rui Li; Cuiping Liu; Weichang Chen; Dong Hua; Xueguang Zhang (Human Genetics, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Overexpression of integrin-linked kinase (ILK) is associated with tumor progression and an unfavorable prognosis in patients with colorectal cancer - Rui Li; Baolin Liu; Hongzhuan Yin; Wei Sun; Jianqiao Yin; Qi Su (Journal of Molecular Histology, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Effects of flue gas desulfurization gypsum by-products on microbial biomass and community structure in alkaline–saline soils - Ming Li; Lili Jiang; Zhaojun Sun; Jinzhi Wang; Yichao Rui; Lei Zhong; Yanfen Wang; Paul Kardol (Journal of Soils and Sediments, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) field strains in south China - Zhi-Li Li; Ling Zhu; Jing-Yun Ma; Qing-Feng Zhou; Yan-Hua Song; Bao-Li Sun; Rui-Ai Chen; Qing-Mei Xie; Ying-Zuo Bee (Virus Genes, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Combined effects of a neutrophil elastase inhibitor (sivelestat sodium) and a free radical scavenger (edaravone) on lipopolysaccharide-induced acute lung injury in rats - Tao Yang; Junjie Zhang; Lulu Sun; Xiaoyan Zhu; Jinbao Li; Jiafeng Wang; Hui Chen; Rui Bao; Xiaoming Deng; Jiong Hou; Yujian Liu (Inflammation Research, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Cellular membrane cholesterol is required for porcine reproductive and respiratory syndrome virus entry and release in MARC-145 cells - Ying Sun; ShaoBo Xiao; Dang Wang; Rui Luo; Bin Li; HuanChun Chen; LiuRong Fang (Science China Life Sciences, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

Integration of gene chip and topological network techniques to screen a candidate biomarker gene (CBG) for predication of the source water carcinogenesis risks on mouse Mus musculus - Jie Sun; Shupei Cheng; Aimin Li; Rui Zhang; Bing Wu; Yan Zhang; Xuxiang Zhang (Ecotoxicology, 2011)

Preliminary evaluation of gene expression profiles in liver of mice exposed to Taihu Lake drinking water for 90 days - Yan Zhang; Weixin Li; Rui Zhang; Jie Sun; Bing Wu; Xuxiang Zhang; Shupei Cheng (Ecotoxicology, 2011)

Genome-wide screening of indicator genes for assessing the potential carcinogenic risk of Nanjing city drinking water - Rui Zhang; Shupei Cheng; Aimin Li; Jie Sun; Yan Zhang; Xuxiang Zhang (Ecotoxicology, 2011)

NMR-based metabolic profiling for serum of mouse exposed to source water - Yan Zhang; Weixin Li; Jie Sun; Rui Zhang; Bing Wu; Xuxiang Zhang; Shupei Cheng (Ecotoxicology, 2011)

Echinococcus granulosus: Immunoprotection accompanyied by humoral and cytokine response against secondary hydatidosis in mice immunized with rEg.myophilin - Junfeng Sun; Yana Wang; Zongji Li; Rui Ma; Haiqing Ji; Ying Xiong; Yin Wang; Zhaoyu Li; Wei Zhao (Veterinary Research Communications, 2011)

Artesunate inhibits growth and induces apoptosis in human osteosarcoma HOS cell line in vitro and in vivo - Qiang Xu; Zhao-xu Li; Hui-qin Peng; Zheng-wang Sun; Rui-lin Cheng; Zhao-ming Ye; Wei-xu Li (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

QTL analysis of kernel shape and weight using recombinant inbred lines in wheat - Xian-Yin Sun; Ke Wu; Yan Zhao; Fan-Mei Kong; Guan-Zhu Han; Hong-Ming Jiang; Xing-Jiao Huang; Rui-Jun Li; Hong-Gang Wang; Si-Shen Li (Euphytica, 2009)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Degradation of Hazardous Dyes in Wastewater using Nanometer Mixed Crystal TiO2 Powders under Visible Light Irradiation - Jun Wang; Ronghe Li; Zhaohong Zhang; Wei Sun; Xiaofang Wang; Rui Xu; Zhiqiang Xing; Xiangdong Zhang (Water, Air, & Soil Pollution, 2008)

Inhibition of Japanese Encephalitis Virus NS1 Protein Expression in Cell by Small Interfering RNAs - Xueqin Liu; Shengbo Cao; Rui Zhou; Gaoyuan Xu; Shaobo Xiao; Ying Yang; Minxuan Sun; Yaoming Li; Huanchun Chen (Virus Genes, 2006)

Development of highly regenerable callus lines and Agrobacterium-mediated transformation of Chinese lawngrass (Zoysia sinica Hance) with a cold inducible transcription factor, CBF1 - Rui-fen Li; Jian-hua Wei; Hong-zhi Wang; Jie He; Zhen-yuan Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)